2019
DOI: 10.2134/jeq2018.07.0265
|View full text |Cite
|
Sign up to set email alerts
|

Catchment‐scale Phosphorus Export through Surface and Drainage Pathways

Abstract: The site‐specific nature of P fate and transport in drained areas exemplifies the need for additional data to guide implementation of conservation practices at the catchment scale. Total P (TP), dissolved reactive P (DRP), and total suspended solids (TSS) were monitored at five sites—two streams, two tile outlets, and a grassed waterway—in three agricultural subwatersheds (221.2–822.5 ha) draining to Black Hawk Lake in western Iowa. Median TP concentrations ranged from 0.034 to 1.490 and 0.008 to 0.055 mg P L−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…Catchment 15 has low mixed BMP coverage (21.4%) by at least one type of BMP and does not receive manure application, but drains effluent from the town of Breda, population 409, along with two AFOs that may contribute to bacteria inputs. Further hydrologic characterization can be found in [19].…”
Section: Site Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Catchment 15 has low mixed BMP coverage (21.4%) by at least one type of BMP and does not receive manure application, but drains effluent from the town of Breda, population 409, along with two AFOs that may contribute to bacteria inputs. Further hydrologic characterization can be found in [19].…”
Section: Site Descriptionmentioning
confidence: 99%
“…Samples were collected at each site in 1 L high-density polyethylene (HDPE) bottles every two weeks in sampling year 2017 and every week in sampling year 2018. The following were the total number of samples collected at each site (2017 and 2018, respectively): S11 (16,33); ST12 (15,33); S15 (19,33); T8 (20, 33); EOC (0, 23). Surface water samples were collected at the mid-point of each stream channel in the highest velocity flow.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harmel, Smith, King, and Slade (2009) estimated the median uncertainty in PO 4 -P concentrations to be ±19%, in TP to be ±23%, and in TSS to be ±18%; however, the uncertainty in dissolved constituents such as DRP receives much of the quality assurance focus due to holding times. Many other studies have reported similar challenges, including Brendel et al (2018), who conducted a study at this same location, although various DRP preservation and storage methods, such as acidification and refrigeration, have been used (Moore & Locke, 2013). Different lengths of holding time have also been reported in different studies (Royer, David, & Gentry, 2006;Sharpley et al, 2008;Stenberg et al, 2012).…”
Section: Data Limitationsmentioning
confidence: 84%
“…As algae may bind nitrogen, an increase in P-availability may trigger algal outbreaks. This has been observed in many cases to occur due to excessive fertilizer and manure applications For many aquatic systems, soil and particulate-P erosion together with runoff water are main sources of inputs of P to surface water (Brendel et al, 2019). Sediment pore water and desorption from its solid phase replenish P in overlying waters, and become available for consumption by aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%